Heavy metals concentrations in commercial organic fertilizers and the potential risk of fertilization into soils - Kunjie Su; Qingliang Zhang; Anjing Chen; Xiaoqin Wang; Lingling Zhan; Qiang Rao; Jinxia Wang; Hongjun Yang (Scientific Reports)
Abstract Inductively coupled plasma mass spectrometry (ICP-MS) was used to detect heavy metals in 74 typical and representative commercial organic fertilizers (COFs) collected in major COF production areas in China. The potential risk of fertilization into soils was evaluated. The concentrations of heavy metals (mg kg− 1) in these COFs were 1.55–36.95 (As), 0.04–2.32 (Hg), 1.43–78.05 (Pb), 0.15–7.49 (Cd), 11.03–212.90 (Cr), 7.74-555.11 (Cu), 21.46-2705.68 (Zn), and 5.62-244.47 (Ni), respectively. Based on China’s Organic Fertilizer Standard (2021), COFs with excessive heavy metals accounted for 45.95% (As), 1.35% (Hg), 2.70% (Pb), 8.11% (Cd), and 6.76% (Cr). According to the European Union standard (2019), the rate of COFs with excessive heavy metals was 32.43% for Cu, 75.68% for Zn, and 85.14% for Ni. Estimated by applying 3854 kg hectare− 1 (dry bass) of fertilizer per hectare per year, to guarantee the safe use of organic fertilizer, the risk monitoring of Cd in soil should be emphasized. China should formulate appropriate standards for the limits of Cu, Zn, and Ni in organic fertilizer as soon as possible and should pay great attention to heavy metal pollution of soils.